Kerja Sama Keluarga, Sekolah, dan Masyarakat dalam Pembinaan Anak - Andi Fadhilah A.Natsir; Jufri Jufri (Universitas Muslim Indonesia, 2022)
Education is something that lasts a lifetime. Education and coaching is the responsibility of all parties, not only the responsibility of the school or the family but also the responsibility of the community. These three institutions, which are referred to as the educational tri-center, establish cooperative relationships to form not only intelligent people, but also those who are cultured, civilized, and religious. The role of the family in fostering children includes providing protection, inculcating religious and scientific values, teaching skills and good behavior, setting rules, providing facilities for children's needs, and creating a comfortable and happy atmosphere. The role of schools in fostering children is as a formal institution that provides facilities in the process of child development as a whole starting from carrying out teaching, guidance, and potential development from various aspects so that they are able to develop in accordance with the expectations and norms that apply in society optimally. The role of the community in fostering children is not only as a service user but also contributes either with funds, goods or labor, participates in school activities or events and participates in making decisions by being part of the school committee.